Trust, Cohesion, and Cooperation After Early Versus Late Trust Violations in Two-Person Exchange: The Role of Generalized Trust in the United States and Japan. (December 2014) - Kuwabara, Ko; Vogt, Sonja; Watabe, Motoki; Komiya, Asuka
We examine how the timing of trust violations affects cooperation and solidarity, including trust and relational cohesion. Past studies that used repeated Prisoner's Dilemmas suggest that trust violations are more harmful when they occur in early rather than later interactions. We argue that this effect of early trust violations depends on cultural and individual differences in generalized trust. A laboratory study from high- and low-trust cultures (the United States vs. Japan) supported our claim. First, early trust violations were more harmful than late trust violations, but only for Americans; the pattern reversed for Japanese. Second, these patterns were mediated by individual differences in generalized trust. Finally, generalized trust also moderated the effect of trust violations in the United States but not Japan. By demonstrating that generalized trust is not only lower but also less important in low-trust cultures, our research advances our understanding of how culture affects the development of solidarity in exchange relations.